The Bioactivity of Xylene, Pyridine, and Pyrazole Aza Macrocycles against Three Representative Leishmania Species - Álvaro Martín-Montes; Álvaro Martínez-Camarena; Alberto Lopera; Irene Bonastre-Sabater; M. Paz Clares; Begoña Verdejo; Enrique García-España; Clotilde Marín (MDPI AG, 2023)
Due to the urgent need for finding effective and free of secondary effect treatments for every clinical form of Leishmaniasis, a series of synthetic xylene, pyridine and, pyrazole azamacrocycles were tested against three Leishmania species. A total of 14 compounds were tested against J774.2 macrophage cells which were models for host cells, and against promastigote and amastigote forms of each studied Leishmania parasite. Amongst these polyamines, one proved effective against L. donovani, another one for L. braziliensis and L. infantum, and another one was selective solely for L. infantum. These compounds showed leishmanicidal activity and reduced parasite infectivity and dividing ability. Action mechanism studies gave a hint that compounds were active against Leishmania due to their ability to alter parasite metabolic pathways and reduce (except Py33333) parasitic Fe-SOD activity.